2017
DOI: 10.1590/1806-9282.63.05.414
|View full text |Cite
|
Sign up to set email alerts
|

Sexual addiction in drug addicts: The impact of drug of choice and poly-addiction

Abstract: Objective:To compare the risk of comorbid sexual addiction in a sample of individuals with a diagnosis of substance dependence, stratifying the sample by drug of choice as well as by mono versus polysubstance addiction. Method: All data were collected at Santa Casa de São Paulo, Brazil. The study sample comprised all alcohol or drug dependents admitted to the Addiction Treatment Unit between November 2013 and August 2014. A generalized linear model with a binomial distribution was performed to compare the odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Two studies investigated CSBD in participants with substance dependence [ 43 , 44 ] who also reported very high CSBD frequency. Diehl et al [ 43 ], reported 28.4% of participants with substance dependence displayed clinically relevant levels of CSBD (measured with SAST).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies investigated CSBD in participants with substance dependence [ 43 , 44 ] who also reported very high CSBD frequency. Diehl et al [ 43 ], reported 28.4% of participants with substance dependence displayed clinically relevant levels of CSBD (measured with SAST).…”
Section: Resultsmentioning
confidence: 99%
“…Diehl et al [ 43 ], reported 28.4% of participants with substance dependence displayed clinically relevant levels of CSBD (measured with SAST). Likewise, Antonio et al [ 44 ] reported that 18.9% of participants with alcohol dependence and even 40.3% with crack/cocaine dependence showed clinically relevant levels of CSBD (SAST).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations